Delivery of antagomiR204-conjugated gold nanoparticles from PLGA sheets and its implication in promoting osseointegration of titanium implant in type 2 diabetes mellitus - Liu X (Dove Medical Press, 2017)
Xiangwei Liu,1,* Naiwen Tan,1,* Yuchao Zhou,1 Hongbo Wei,1,* Shuai Ren,1 Fan Yu,2 Hui Chen,3 Chengming Jia,4 Guodong Yang,5 Yingliang Song1 1State Key Laboratory of Military Stomatology & National Clinical Research Center for Oral Diseases & Shaanxi Engineering Research Center for Dental Materials and Advanced Manufacture, Department of Implant Dentistry, 2Department of Prosthodontics, School of Stomatology, 3Department of Plastic Surgery, Tangdu Hospital, 4Department of Traditional Chinese Medicine, Xijing Hospital, 5Department of Biochemistry and Molecular Biology, Fourth Military Medical University, Xi’an, China *These authors contributed equally to this work Abstract: Impaired osseointegration of the implant remains the big hurdle for dental implant therapy in diabetic patients. In this study, the authors first identified that miR204 was strikingly highly expressed in the bone mesenchymal stem cells (BMSCs) of diabetic rats. Forced expression of miR204 repressed the osteogenic potential of BMSCs, while inhibition of miR204 significantly increased the osteogenic capacity. Moreover, the miR204 inhibitor was conjugated with gold nanoparticles (AuNP-antagomiR204) and dispersed them in the poly(lactic-co-glycolic acid) (PLGA) solution. The AuNP-antagomiR204 containing PLGA solution was applied for coating the surface of titanium implant. Electron microscope revealed that an ultrathin sheet was formed on the surface of the implant, and the AuNPs were evenly dispersed in the coated PLGA sheet. Cellular experiments revealed that these encapsulated AuNP-antagomiR204 were able to be released from the PLGA sheet and uptaken by adherent BMSCs. In vivo animal study further confirmed that the AuNP-antagomiR204 released from PLGA sheet promoted osseointegration, as revealed by microcomputerized tomography (microCT) reconstruction and histological assay. Taken together, this study established that miR204 misexpression accounted for the deficient osseointegation in diabetes mellitus, while PLGA sheets aided the release of AuNP-antagomiR204, which would be a promising strategy for titanium implant surface functionalization toward better osseointegration. Keywords: osseointegration, miR204, PLGA sheets, gold nanoparticles, diabetes mellitus, titanium implant